STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU SD NEGERI - Dewi, Yenti; Iskandar, Iskandar; Zahriyanti, Zahriyanti (Universitas Indraprasta PGRI, 2024)
This study aims to analyze the principal's strategies in enhancing teacher professionalism at SD Negeri 2 Lut Tawar, focusing on the formulation, implementation, and evaluation of strategies. The research adopts a descriptive qualitative approach, allowing for in-depth exploration of the principal's managerial policies and practices. Data collection techniques include interviews with the principal and teachers, observations, and document analysis. The findings reveal that in strategy formulation, the principal emphasizes the importance of leadership by example and discipline, involving teachers in discussions, and identifying relevant technological needs for learning. In strategy implementation, the principal assigns tasks based on teachers' competencies and integrates technology into the teaching-learning process. A reward and punishment system is also applied to motivate teachers to improve their performance. Furthermore, strategy evaluation is conducted regularly through classroom observations, evaluation meetings, and gathering feedback from students and parents. The evaluation results are used to adjust strategies and ensure the relevance of policies to the school's needs. This evaluative approach fosters continuous improvement and consistent development of teacher professionalism. The study concludes that a combination of participatory formulation, appropriate strategy implementation, and measurable evaluation creates a conducive environment for improving teacher professionalism. The implications of this research provide input for educational departments, principals, and teachers in developing more effective school management.